Jerry Pentland interviewed by Fred Morton in the Australian aviators in World War I oral history project - Pentland, Jerry (Alexander Augustus Norman Dudley), 1894-1983; Morton, Fred, 1930-1993 (1976)
Reel 6. Side 1: Pentland talks about his World War I service as a fighter pilot; the AIF in Gallipoli with 12th Light Horse; his training as a pilot, May 1916; planes he flew including BE12's and Bristol Scouts; flying instruction; experiences in France with 19 Squadron 1916-1917; attitude of British towards Australians; difficulties getting into Royal Flying Corps; Stag aircraft; battle of Ypres.
Digital master available
Jerry Pentland was born August 1894; Royal Flying Corps, 16, 19 & 87 Squadrons; one of the highest scoring aces in World War 1. Enlisted in Royal Flying Corps in London in 1915. In May 1915 sent to France. His first squadron was 16 on BE's (British Experimental aircraft). He transferred to 29 Squadron where he became a scout or fighting pilot on DH2's. When 56 Squadron was being formed he was picked to command a flight but was switched to 19 at the last moment. He shot down 6 German planes and was shot down himself and injured. After recovering he was put in charge of training at Hendon and later London Colney. He returned to France being nominally attached to 84 Squadron, with a roving commission. He was awarded a DFC after 18 hits. His final tally was 24.
Timed summary available.
Keywords: Pentland, Jerry -- 1894-1983 -- Interviews; Fighter pilots -- Australia -- Interviews; World War, 1914-1918 -- Aerial operations, Australian -- Personal narratives; Air pilots -- Australia -- Interviews